Peran Camat Sebagai Fasilitator Dalam Penyusunan Laporan Penyelenggaraan Pemerintahan Desa Jangkar Asam - Melta Indah Nurhayati (Simbur Cahaya, 2018)
The Role of Head of Gantung Sub-distric as a Facilitator in The Preparation of Jangkar Asam’s Village Governance Implementation Reportatthe end of Fiscal Year 2015. This study describes the role of head of Gantung sub-distric (Camat Gantung) as a facilitator in the preparation of Jangkar Asam’s village governance implementation (LPPDes) reportat the end offiscal year 2015. This research is qualitative descriptive interpretive. The data were collected by means of deep interview. The researcher suggests that the Headof Belitung Timur regency needs to issue a regent regulation that clearly defines forms and limits of facilitation rolesthat should be done by Camat Gantung. In term of enhancing the facilitative and skill role of providing supports and organizing, Camat Gantung and his staff need to improve their competences by following the education and training, technical guidance and workshop about community worker and they also need to build cooperation with the other community workers to assist the Village Government of Jangkar Asam. For applying the role and skill facilitation of social animation, utilization of skill and resource and personal communication, Camat Gantung need to multiply the interaction with Village Government of Jangkar Asam in formal meetings such as open dialoge and discussion and non-formal meetings such as individual consultation and coordination.